2006
DOI: 10.1021/jp0551770
|View full text |Cite
|
Sign up to set email alerts
|

Strong Two-Photon Absorption in New Asymmetrically Substituted Porphyrins:  Interference between Charge-Transfer and Intermediate-Resonance Pathways

Abstract: We study two-photon absorption (2PA) in two series of new free-base porphyrins with 4-(diphenylamino)stilbene or 4,4'-bis-(diphenylamino)stilbene (BDPAS) attached via pi-conjugating linkers at the porphyrin meso-position. We show that this new substitution modality increases the 2PA cross section in the Soret band region (excitation wavelength 750-900 nm) of the core porphyrin by nearly 2 orders of magnitude, from sigma(2) approximately 10 GM for the meso-phenyl-substituted analogue to sigma(2) approximately 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
141
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 162 publications
(147 citation statements)
references
References 68 publications
5
141
0
1
Order By: Relevance
“…41 The TPA cross-sections of this series of conjugated porphyrin 235 dimers compare favourably with the values of other potential photosensitisers designed for two-photon excited PDT. For example, TPA cross-sections of ca 2000 GM have been reported for tetraphenyl-porphycenes (determined via two-photon excited singlet oxygen detection), 18 ca 1000 GM for porphyrin-TPA chromophore 240 assemblies (determined via two-photon excited fluorescence, similar to the present work) 19 and 7900 GM for self-assembled porphyrin dimers (determined by the z-scan technique). 24 The high TPA efficiencies of our porphyrin dimers within the 'therapeutic window' of biological tissues (700-950 nm) 4 in 245 combination with the high singlet oxygen quantum yields highlight these compounds as promising photosensitisers for two-photon excited PDT.…”
Section: Two-photon Absorption Spectrasupporting
confidence: 83%
“…41 The TPA cross-sections of this series of conjugated porphyrin 235 dimers compare favourably with the values of other potential photosensitisers designed for two-photon excited PDT. For example, TPA cross-sections of ca 2000 GM have been reported for tetraphenyl-porphycenes (determined via two-photon excited singlet oxygen detection), 18 ca 1000 GM for porphyrin-TPA chromophore 240 assemblies (determined via two-photon excited fluorescence, similar to the present work) 19 and 7900 GM for self-assembled porphyrin dimers (determined by the z-scan technique). 24 The high TPA efficiencies of our porphyrin dimers within the 'therapeutic window' of biological tissues (700-950 nm) 4 in 245 combination with the high singlet oxygen quantum yields highlight these compounds as promising photosensitisers for two-photon excited PDT.…”
Section: Two-photon Absorption Spectrasupporting
confidence: 83%
“…Photodynamic therapy (PDT) uses a light-activated drug, 25 known as a photosensitiser, to treat neoplastic diseases. [1][2][3][4][5][6][7][8] The treatment is relatively benign and gives good cosmetic outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25][26] Recently, focus has turned to compounds for two-photon excited PDT, although only a few of these have shown in vitro activity and few in vivo studies have been published. 27-33 60 We have recently reported a family of ionic conjugated porphyrin dimers with peak TPA cross-sections as large as 17,000 GM (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigations have demonstrated that the twophoton transition in the long pulse case can be greatly enhanced due to the presence of the PDM in the medium [32,33]. As a result, the medium initially absorbs energy from the pulse by two-photon transition, and then reemits it back at the resonant frequency of the medium (ω 0 = 2ω p ).…”
Section: Resultsmentioning
confidence: 99%